Corruption Criminal Study in the Sphere of Russian Federation Local Government - Aglyamova, Gulnaz M.; Musabirova, Dinara A.; Talan, Mariya v.; Khamitov, Radik N. (Journal of History Culture and Art Research, 2017)
The purpose of the study is the criminological analysis of a criminal identity who commits corruption crimes in the sphere of local self-government. Based on dialectical materialistic methodology use and the survey method, it is revealed the main signs, classifications and typologies of a criminal's personality, who commits corruption crimes in this sphere. Effective preventive measures are proposed to reduce the number of persons committing corruption crimes. The results suggest that there is desire to illegally enrich through the abuse of authority and the underestimation of municipal employee work by state bodies. Therefore, ti is necessary to pay attention to the mechanisms of disposition and sanction implementation concerning the norms of criminal legislation in law enforcement practice.